Synthesis of 1,3-benzoxazines Based on 2,4,4-trimethyl-7,2’,4’-trihydroxy Flavan: Antibacterial, Anti-inflammatory, Cyclooxygenase-2 Inhibition and Molecular Modelling Studies - Mohammed, Issam Ahmed; Ahmed, Mahmood; Ikram, Rabia; Muddassar, Muhammad; Qadir, Muhammad Abdul; Awang, Khalijah (Bentham Science Publishers, 2018)
Background: In the present study, the formation of 2, 4, 4-trimethyl-7,2’4’-trihydroxy flavan has been used as the key feature for the formation of new 1,3-benzoxazines. This reaction was carried out via Mannich-condensation reaction, the 7-hydroxy group of flavan was reacted with different primary amines in the presence of formaldehyde. Methods: All the synthesized compounds were characterized on the basis of FT-IR, NMR, MS and elemental analysis (CHN). Disk diffusion and 96-well plate assay methods were employed for the zone of inhibition and minimum inhibitory concentration determination, respectively to investigate the antibacterial activities. Results and Conclusion: Our studies showed that compound with electron withdrawing group on the benzene ring of 1,3-benzoxazines has promising antibacterial activities. An oral dose of 10 mg/kg body weight was administered to albino mice for acute toxicity of synthesized compounds. In vivo anti-inflammatory and in-vitro cyclooxygenase-2 (COX-2) studies showed that compound 11 was the most potent anti-inflammatory agent which inhibited induced edema by 62.7% while 68.7% inhibition of COX-2 was observed. The plausible binding mode of this compound in COX-2 enzyme was also determined using molecular docking simulations.